The Emotional Effect of Background Music on Selective Attention of Adults - Nadon, Éva; Tillmann, Barbara; Saj, Arnaud; Gosselin, Nathalie (Frontiers in Psychology, 2021)
Daily activities can often be performed while listening to music, which could influence the ability to select relevant stimuli while ignoring distractors. Previous studies have established that the level of arousal of music (e.g. relaxing/stimulating) has the ability to modulate mood and affect the performance of cognitive tasks. The aim of this research was to explore the effect of relaxing and stimulating background music on selective attention. To this aim, 46 healthy adults performed a Stroop task in five different sound environments: relaxing music, noise-matched relaxing music, stimulating music, noise-matched stimulating music, and silence. Results showed that response times for incongruent and congruent trials as well as the Stroop interference effect were similar across conditions. Interestingly, results revealed a decreased error rate for congruent trials in the relaxing music condition as compared to the noise-matched relaxing music condition, and a similar tendency between relaxing music and noise-matched stimulating music. Taken together, the absence of difference between background music and silence conditions suggest that they have similar effects on adult’s selective attention capacities, while noise seems to have a detrimental impact, in particular when the task is cognitively easier. In conclusion, the type of sound stimulation in the environment seems to be a factor that can affect cognitive tasks performance.